Identifying critical elements of road infrastructure using cascading impact assessment - Rehak, David; Patrman, David; Brabcová, Veronika; Dvořák, Zdeněk (Transport, 2020)
Road transport is a key means of transporting people and cargo on land. Its particular advantages are speed and operability, which are balanced, however, by dependence on road infrastructure. Road infrastructure reliability is an important factor in its functioning. If some elements of road infrastructure are disrupted or fail, the function of dependent infrastructures, such as the integrated rescue system or industry, are also impaired and may fail. These important elements of road infrastructure should be identified as critical and be given greater attention when identifying weaknesses and implementing subsequent security measures. This article introduces the Identifying Critical Elements of Road Infrastructure (ICERI) method, which was designed to make use of Cascading Impact Assessments (CIA). The use of CIA allows critical elements to be identified through impact escalation analysis. These impacts can therefore be monitored not only in road transport infrastructure but also across the entire critical infrastructure system. First published online 4 May 2020